Analgesics and Sport Performance: Beyond the Pain‐Modulating Effects. Issue 1 (4th August 2017) - Holgado, Darias; Hopker, James; Sanabria, Daniel; Zabala, Mikel
Abstract: Analgesics are used widely in sport to treat pain and inflammation associated with injury. However, there is growing evidence that some athletes might be taking these substances in an attempt to enhance performance. Although the pharmacologic action of analgesics and their use in treating pain with and without anti‐inflammatory effect is well established, their effect on sport performance is debated. The aim of this review was to evaluate the evidence of whether analgesics are capable of enhancing exercise performance and, if so, to what extent. Paracetamol has been suggested to improve endurance and repeated sprint exercise performance by reducing the activation of higher brain structures involved in pain and cognitive/affective processing. Nonsteroidal anti‐inflammatory drugs affect both central and peripheral body systems, but investigation on their ergogenic effect on muscle strength development has provided equivocal results. The therapeutic use of glucocorticoids is indubitable, but clear evidence exists for a performance‐enhancing effect after short‐term oral administration. Based on the evidence presented in this review article, the ergogenic benefit of analgesics may warrant further consideration by regulatory bodies. In contrast to the aforementioned analgesics, there is a paucity of research on the use of opioids such as tramadol on sporting performance. Level of Evidence: III